Determinants of Islamic Banks Acceptance in Oman - Mohammed, Shariq; Sha, Nadia; Uddin, Mohammed Ahmar (International Review of Management and Marketing, 2017)
This paper discusses about the inception of Islamic Banking in Oman. This paper would discuss the Islamic Banking Regulatory Framework (IBRF) under which the Islamic banking system is operating. The two full fledged banks which are working in Oman are Alizz Islamic Bank, Bank Nizwa and there are 6 Islamic windows which are working in Oman. The study would be related to the factors which influence the customers’ attraction towards Islamic Banking in Oman. Keywords: Central Bank of Oman (CBO), Royal Decree 69/2012, Islamic Banking Regulatory Framework, Fully-fledged Islamic banks, Window model of Islamic Banks JEL Classifications: E59, K20, G20, G21, G29